TOURISM IN LIMON: DATA AND ELEMENTS OF ANALYSIS ABOUT THE DYNAMIC OF THE LABOR ACTIVITIES. THE CASE OF BARRIO PACUARE, LOCATED IN THE CENTRAL CANTON - Carballo Chaves, Pablo (2014)
This paper brings the main results achieved by the proyect: Centros Históricos del Turismo(ucr) ―Tourism historial centers (ucr)― operating for more than two years. After a technicalcleaning, obtained several data from the Pacuare neighborhood ―Barrio Pacuare― located inthe Limon central canton in Costa Rica. It has been created a laboral typology with these segments: Tourism, Public, Formal, Informal-Domestic, and Others, all this segments arefor the individual data base. In the case of the home data base it has been incorporated:unoccupied. We present data that help to the discussion and reflection about tourism, andlabor situation of Limón, especially in the Pacuare case.